Experimental and numerical studies on hysteretic behavior of friction-strip coupled damper. (15th August 2022) - Lu, Yujie; Liu, Ye; Ge, Qi; Lv, Qingfang; Wang, Zhengqi
Highlights: Proposal of a novel friction-strip coupled damper. Low-cycle fatigue tests on eight FSCD specimens including four parameters. Numerical analyses on distinctive hysteretic behaviors of two modules of the FSCD. Abstract: Aiming at solving the issue of conventional metallic and friction dampers, this paper proposes a novel friction-strip coupled damper (FSCD) by setting friction and strip modules in parallel. The coupled working mechanism endows the damper to provide sufficient energy dissipation along with stiffness for main structures. Quasi-static tests were conducted on eight FSCD specimens to investigate the effect of the friction force, the strip number, the strip width and the strip configuration on the hysteretic behavior of the FSCD. The test results verified the effectiveness of the three-stage working mechanism, i.e., the collaborative stage, degradation stage and friction-only stage, and demonstrated that the strength, energy dissipation and stiffness of the FSCD increased with the friction force, the strip width and the strip number. The strip with a larger chamfer radius brought no improvement in the seismic performance of the FSCD, whereas the FSCD with strips adopting a modified elliptic-arc edge presented higher strength, better energy dissipation capacity and stiffness. Moreover, a detailed numerical model considering the ductile damage behavior was established and validated. The numerical result matched well with the test one in terms of the hysteretic performance, energy dissipation and stiffness of the FSCD. Besides, the gradual fracture of strips was also clearly captured by the finite element model.